The Naples prognostic score as a new predictive index of severe abdominal aortic calcification: a population-based study - Tan, Qiang; Zhang, Jian; Peng, Yanrong; Yang, Rui; Zhu, Yanbin; Yong, Xi; Yin, Hongshun; Zheng, Jianghua (Frontiers in Cardiovascular Medicine, 2025)
PurposeAbdominal aortic calcification (AAC) is related to inflammation and nutritional status. The Naples prognostic score (NPS) is an innovative biological marker capable of reflecting systemic inflammation and nutritional status. This research seeks to investigate the correlation of NPS with severe abdominal aortic calcification (SAAC).MethodsThe research evaluated data obtained from the National Health and Nutrition Examination Survey (NHANES) conducted between 2013 and 2014. The variables were filtered utilizing the Least Absolute Shrinkage and Selection Operator (LASSO) regression. Weighted logistic regression models were employed to examine the association of NPS with SAAC. The predictive value of NPS for the risk of SAAC was assessed utilizing the receiver operating characteristic (ROC) curve. A subgroup analysis was conducted to assess the strength and reliability of the research findings.ResultsThe research encompassed 2,854 participants, among whom 303 (11.87%) exhibited SAAC. The outcomes of multivariate weighted logistic regression revealed that participants with a NPS of 3–4 points was positively correlated with SAAC in comparison to the control group [odds ratio (OR) = 2.07, 95% confidence interval (95%CI): 1.17–3.67]. The area under the curve (AUC) for predicting the risk of SAAC using NPS was 0.635. The subgroup analysis results indicated that there was no significant difference noted in the association of NPS with SAAC across various population subgroups.ConclusionA positive association of NPS with SAAC has been observed in this research. This study offers valuable insights into the prevention and diagnosis of SAAC. Future longitudinal studies are warranted to confirm causative relationships and assess the role of NPS in clinical decision-making for SAAC.